IDENTIFIKASI AWAL POTENSI EKSTRAK ETANOL RIMPANG JAHE MERAH (Zingiber officinale Rosc. var. rubrum) SEBAGAI OBAT OSTEOPOROSIS - Aqnes Budiarti; Devi Nisa Hidayati; Nur Aini (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Reduced bone density is an indication of osteoporosis. The study of osteoporosis is conducted by measure the influence of triggering compound to the enhancement of  bone density of ovariectomized rat that have been lifted ovaries. Ovariectomy caused rats have been deficiency of estrogen hormone  whose function  to maintain bone density.Compound  that can increase bone density has the potential as osteoporosis drug. Red ginger rhizome  contains flavonoid compound  as phytoestrogen  whose  estrogenic effect that can replace the function of estrogen. Flavonoid  is easy to be solved  in ethanol so that was extracted using ethanol. The purpose of this study was to measure  the enhancement of bone density of ovariectomized rats due to the trigger of ethanol extract of red ginger (EERJM). Research was  conducted  experimentally  to the female Wistar rats by the  post test  only controlled group design. Treatment was given for 30 days and  the determination of bone density using Dual X-Ray radiography method. Data of bone density values were statistically analyzed by One Way ANOVA followed by Tukey test. The results showed that  the administration of EERJM dose 500 and 1000 mg/kg BW enhanced bone density of ovariectomized rat. Keywords: bone density, ovariectomized rat, red ginger, osteoporosis